2008
DOI: 10.1080/08858190802039136
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Radiotherapy Knowledge Among Community Family Physicians and Nurses

Abstract: More education regarding PR is required for primary care physicians and nurses caring for cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…In the context of radiotherapy this is of concern because the data are consistent with the published literature on clinical practice (Samant 2001;Lutz et al 2004Lutz et al , 2007Samant et al 2006;Berrang & Samant 2008) in which not all patients have been appropriately advised or referred. In the context of radiotherapy this is of concern because the data are consistent with the published literature on clinical practice (Samant 2001;Lutz et al 2004Lutz et al , 2007Samant et al 2006;Berrang & Samant 2008) in which not all patients have been appropriately advised or referred.…”
Section: Resultssupporting
confidence: 56%
“…In the context of radiotherapy this is of concern because the data are consistent with the published literature on clinical practice (Samant 2001;Lutz et al 2004Lutz et al , 2007Samant et al 2006;Berrang & Samant 2008) in which not all patients have been appropriately advised or referred. In the context of radiotherapy this is of concern because the data are consistent with the published literature on clinical practice (Samant 2001;Lutz et al 2004Lutz et al , 2007Samant et al 2006;Berrang & Samant 2008) in which not all patients have been appropriately advised or referred.…”
Section: Resultssupporting
confidence: 56%
“…Studies from Canada and the Netherlands have also reported that some GPs may have limited knowledge about the indications for palliative radiotherapy (Samant et al . ; Berrang & Samant ; Vulto et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, our previous work with Australian GPs offers some evidence that patients with advanced cancer are not always referred appropriately or in line with specialist practice. Studies from Canada and the Netherlands have also reported that some GPs may have limited knowledge about the indications for palliative radiotherapy (Samant et al 2006;Berrang & Samant 2008;Vulto et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations